Pengaruh Circuit Training Terhadap Daya Tahan Atlet Cabang Olahraga Handball - Agung Rizki; Z Arifin; Alam Hadi Kosasih; Ani Kurniawati (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. This study aimed to determine the effect of circuit training exercises on the endurance of handball athletes. An experimental method with a pre-experimental design was employed, specifically using a one-group pre-test and post-test design. The research sample comprised 10 handball athletes from the UKM Handball University of Garut, selected due to their low levels of physical endurance. These participants engaged in a circuit training program tailored to enhance their endurance over a designated period. Materials and Methods. This study employed a pre-experimental design with a one-group pre-test and post-test approach. A sample of 10 handball athletes with low physical endurance was selected. Participants underwent a circuit training program over a set period. Endurance was assessed using the Bleep test for cardiovascular endurance and the push-up test for upper body muscular endurance. Data were collected before and after the intervention to evaluate changes in performance. Results. The results indicated a significant improvement in both endurance measures after the circuit training intervention. The athletes showed a 32.30% increase in their Bleep Test scores and a 34.53% improvement in the number of push-ups performed. Conclusions. The results indicate that circuit training exercises significantly improve the endurance of handball athletes. With a notable increase in both cardiovascular and muscular endurance, as evidenced by the Bleep test and push-up test results, circuit training proves to be an effective method for enhancing athletic performance. These findings suggest that incorporating circuit training into regular training routines can benefit athletes seeking to improve their endurance.